The Effect of Waste Disposal in Namatala Ward, Industrial Division Mbale City - Bukhaki Irene (Uganda Christian University, 2024)
The study examined the effect of waste disposal on the environment in Namatala ward Industrial Division, Mbale City. Study objectives explored the Different Methods of Waste Disposal that exist, determined the effects of Waste Disposal on the Environment and the appropriate interventions and Strategies for waste disposal in Namatala Ward, Industrial Division, Mbale City. The researcher adopted a cross-sectional survey design with a mixed-method paradigm that combines qualitative and quantitative methodologies. Key informants of the study were local leaders, industrial division officials and community. The sampling techniques were; census Inquiry and Simple Rando. A consideration of a study population of 60 respondents was considered out of which a sample size of 52 was considered for the study. Data was collected through a survey method, interviews and observations to compile data for the study. About the Different Methods of Waste Disposal that exist in Namatala Ward, Industrial Division, Mbale City. Findings indicated that the recycling, composting, incineration, landfills, dumping on Open spaces, burning waste in Open Ares and the use of Waste Management services such as garbage collection are the many different methods of waste disposal that exist in Namatala Ward, Industrial Division, Mbale City. By examining the effects of Waste Disposal on the Environment in Namatala Ward, Industrial Division, Mbale City. It was found out that the waste disposal degrades the soil quality and water quality, open burning of waste contributes heavily to air pollution, dumping of waste in rivers and lakes leads to destruction of aquatic ecosystem, Recycling reduces the amount of pollution entering the environment, Composting organic waste improves soil fertility and reduces the need for chemic fertilizers, Incineration of waste releases harmful gases that contributes to global warming and Proper waste management greatly reduces the negative impact on the environment while the appropriate interventions and Strategies for waste disposal in Namatala Ward, Industrial Division, Mbale City were implementing strict waste segregation policies, promoting community awareness campaigns on proper waste disposal, providing incentives for recycling and composting, establishing more recycling centers in the community, enforcing penalties for illegal dumping and open burning, investing modern waste treatment and disposal technologies and supporting public private partnerships in waste management. In conclusion, effective waste management involves a multifaceted approach that includes strategies such as proper waste segregation, recycling, composting, community awareness campaigns, and investment in advanced technologies. Supporting public-private partnerships and enforcing penalties for illegal dumping and open burning also play vital roles. These strategies collectively reduce environmental pollution, conserve resources, and promote sustainability. By integrating these practices, communities can achieve more efficient waste management, protect public health, and contribute to a healthier environment. It is recommended that there is need to implement and enforce strict waste segregation policies at the household and commercial levels. Establish more accessible recycling centers and provide regular collection services for recyclables to enhance recycling rates, reduces landfill waste, and promotes resource recovery. There is need to implement comprehensive waste segregation programs at the source, categorizing waste into recyclables, organics, and hazardous materials and reduces contamination of recyclable materials, improves waste processing efficiency, and minimizes environmental pollution.